Evaluation of Implant Success in Patients with Dental Aplasia. (19th June 2019) - Attia, Sameh; Schaper, Ella; Schaaf, Heidrun; Pons-Kühnemann, Jörn; Schlenz, Maximiliane Amelie; Streckbein, Philipp; Böttger, Sebastian; Howaldt, Hans-Peter; Wilbrand, Jan-Falco
Abstract : Introduction . Dental aplasia is an anomaly in which the number of teeth is reduced. It is the most commonly occurring dental anomaly during tooth development. Treatment management of patients with dental aplasia is challenging. Objectives. The aim of this retrospective clinical study was to analyze the survival and success rates of dental implants placed in hypodontic patients, rated with different criteria. Methods. Forty-three patients were diagnosed with dental aplasia and treated with dental implants between November 2000 and February 2016. The variables assessed included the plaque level, bleeding on probing, probing depth, implant mobility, implant stability, and implant loss. To analyze the peri-implant bone level, a panoramic X-ray of each patient was taken. The results were compared with X-rays taken immediately after implantation. Results . Thirty-seven patients (16 males; 21 females) participated in this study. In total, 155 implants (86 maxillary; 69 mandibular) were inserted. Two of the 155 implants failed; the in situ survival rate was 98.7%. The success rate according to the criteria of Buser et al. was 96.8%, and that according to the criteria of Albrektsson et al. was 88.4%. Conclusion. The survival and success rates of dental implants in patients with congenitally absent teeth were very high and did not differ significantly from results achieved in an unaffected population. Dental implants are a reliable therapy for patients with dental aplasia.